Como falar de si mesmo no videoclipe? A música popular massiva como parte constituinte de um sujeito inacabado // How to talk about yourself in the music video? Pop music as a constituent part of an unfinished subject - Janotti Jr, Jeder Ailveira; Alcântara, João André da Silva (Contemporanea, 2016)
ResumoEste artigo parte da análise do videoclipe “Amor Marginal”, de Johnny Hooker, para compreender como as discussões sobre “autenticidade” na música popular massiva são entrecortadas pelos “relatos de si”, mostrando que há uma tessitura da intriga em torno da construção dos personagens musicais que envolvem diferentes suportes, materialidades e interrelações entre gender e genre. Como procedimento metodológico, desenvolvemos uma cartografia de construções de relatos de si mesmo a partir de entrevistas, críticas, canção e videoclipe de Johnny Hooker.SubjectThis article goes through a music video analysis "Amor Marginal", by Johnny Hooker, to understand how discussions about "authenticity" in the pop music are punctuated by "reports of yourself", showing that there is a formation of intrigue surrounding the construction of musical characters involving different media, materiality and interrelations between gender and genre. As methodological procedure, a cartography of constructions reports of yourself from interviews, reviews, song and music video by Johnny Hooker.